2014
DOI: 10.1136/emermed-2013-202930
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic rapid sequence intubation in patients with non-traumatic coma

Abstract: Paramedic RSI in patients with non-traumatic coma has a high procedural success rate. Further studies are required to determine whether this procedure improves outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…). The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
“…These survival differences might be related to varying levels of illness severity between these pathologies, with haemorrhagic strokes having poorer prognosis compared to toxidromes and seizures. Some question the value of routinely intubating seizures and toxidromes in the emergency setting …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported p = 0.046, using a Pearson Chi‐squared test and the full Conclusion in the Abstract was “In adults with severe TBI, prehospital RSI by paramedics increases the rate of favourable neurologic outcome at 6 months compared with intubation in the hospital.” The absence of statistical significance for the primary outcome and all other secondary outcomes were not mentioned in the Conclusion. Subsequently, the RSI protocol was implemented in Victoria for routine use by road‐based paramedics in all patients with coma (Glasgow Coma Score ≤ 9) of both traumatic and nontraumatic causes …”
Section: Examplesmentioning
confidence: 99%
“…Bernard et al from Victoria, Australia found that 49% of all RSIs in their emergency medical service (EMS) are on patients with a non-traumatic coma such as stroke and seizures (based on paramedic diagnosis). 6 Non-traumatic brain pathologies (NTBP) is defined as an acquired brain injury (either permanent or transient) that includes brain tumours, meningitis, encephalitis, hypoxic/anoxic brain injury, stroke, arteriovenous malformations, tumours, aneurysms, brain haemorrhage, as well as brain injury due to diabetes, seizures and toxicity, metabolic conditions and alcohol and drug overdose. [7][8][9] Whilst the prevalence of RSI for non-traumatic coma has been examined, the prevalence and survival outcomes for NTBP patients receiving paramedic RSI needs quantification.…”
Section: Introductionmentioning
confidence: 99%